Personal and logical characteristics involving choosing a conjugal partner - Calin, Mariana Floricica; Sandu, Mihaela Luminita; Eftimie, Madalina (Technium Social Sciences Journal, 2021)
We often talk about the couple, what it means and what is involved, but we seldom recognize it`s true value. The couple is the one who leads to the perpetuation of the human species, it is the first step towards the spread of the human life on Earth. In order for two people to form a family, they need to go through the stage of couple, either married or not. Most people prefer that a couple status is achieved through legal recognition, marriage, then when the first child is born, they become a family. Each of us reaches a moment in life when the preoccupation, interest, curiosity and desire to choose a partner, to start a family appear. We all have our own and different experiences, but we certainly have many things in common. There is a unique intertwining of psychological and social factors that influence and determine an individual in making the right choices.Thus, the need to be part of a couple for some, or to start a family for others, is a need manifested similarly, but named differently. People are social, affective beings and the need to share feelings is common to all. Each individual has unique criteria that they meet when choosing a partner, and I believe that these criteria come from the intertwining of unique personality factors and the importance given by each to social factors that can be involved in forming, developing and maintaining a better relationship.